Nsg ̂-continuous functions in Nano Topological Spaces - et. al., V.Rajendrana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper focuses on -continuous functions (nano semi -continuous functions) in nano topological spaces and certain properties are investigated. We also investigate the concept of -continuous functions and discussed their relationships with other forms of nano continuous functions. Further, we have given an appropriate examples to understand the abstract concepts clearly.